Strategic plan outline for St. Vincent & the Grenadines Bureau of Standards 2001-2005 : [draft] - Harnanan, Bertrand ([CARICOM Secretariat] [Georgetown]GY, 2001)
Deals with the major activities, organizational structure, and staffing requirements. Focuses on a training plan. a recruitment expenditure programme, a capital expenditure programme, and a cost recovery programme. Presents an operational procedures manual.